Matters of judicial practice of Sevastopol and the Republic of Crimea in the field of merchant shipping - Vasiliev Stanislav Aleksandrovich (SHS Web of Conferences, 2021)
Merchant shipping is one of the most demanded types of transportation in the modern world. According to some reports, up to 80% of all cargo is transported by sea. In this regard, the issues of legal regulation of this complex and full of implementation nuances activity acquire particular importance. The specific condition of such seaports as Sevastopol and several other ports on the Crimean Peninsula is since Russia is under the influence of negative economic measures (“sanctions”) imposed by a large number of foreign states. Under these conditions, with the same effect of international and Russian legislation in the entire territory of the Russian Federation, the nature of their application in some cases has a certain specificity concerning these territories. In this regard, the analysis of judicial practice in this area was of particular interest. The purpose of this study is to analyze judicial practice from the point of view of the implementation of international and Russian law norms in the field of merchant shipping, as well as to identify certain trends in the activities of the subjects of the relevant legal relations. Analysis, synthesis, the comparative method, and the method of expert assessments are the methods used in the preparation of this work. The following structural analysis of the available material was used: first, the judicial practice was studied, only after that the work with legislation and other sources was carried out. As a result of the performed research, some problematic aspects of the legal regulation of merchant shipping in Russia have been identified. The trends based on which the Russian maritime law can be transformed have also been identified. The novelty of the research lies in the combination of proposals for further improvement and law enforcement practice in the field of merchant shipping.